Dimensi Penafsiran Dakwah wal Harakah dalam Alqur’an Menurut Tafsir Al –Azhar (Studi terhadap Ayatayat Amar Ma’ruf Nahi Munkar) - Hidayatullah, Taufiq; Jamal, Khairunnas; Gani, Erman (Jurnal An-Nur, 2024)
This study discusses the interpretation of da'wah wal harakah in the Qur'an, a study of the verses of tabligh and amar ma'ruf nahi munkar. Da'wah harakah is a da'wah movement, this da'wah phenomenon occurs today where this da'wah harakah combines the concepts of thought and movement. This means that the waqi'yyah (realistic) Islamic movement is a sociological and functional Islamic movement. Then harakiyyah (dynamic) Islamic movement has its own stages, and has a fixed goal or method of movement that does not justify all means. So this research examines harakah da'wah according to al-Azhar tafsir. This research is library research. And the methodology used is thematic methodology. The data related to this study were collected through literature studies and presented with descriptive analysis techniques, namely by explaining the verses per verse related, by referring to the Qur'an and tafsir books as primary data and books, journals related literature as secondary data. The results of this study are harakah da'wah by conveying revelations from Allah SWT by eradicating evil among the community, using good sentences so that it can be easily understood.